العوامل الاجتماعية المؤدية لعنف التلميذ ضد الأستاذ لدى تلاميذ المرحلة المتوسطة - حمداني، سعاد, بوزيد، ريم (جامعة الوادي university of Eloued, 2017)
Study Summary: The objective of this study was to know the factors of school violence in the Wilayat of Wadi, especially the social factors related to the violent student, and we conducted this study due to the gravity of the phenomenon and the subject was formulated the main question as follows: - Are social factors related to the violence of the student against the professor? Under this main question are sub-questions: - Are family factors related to the violence of the student against the professor? - Is the economic factors related to the violence of the student against the professor? - Are school factors related to the violence of the student against the professor? In our study, we discussed the following hypotheses: General Hypothesis: - There is a relationship between the social factors and the violence of the student against the professor. The general hypothesis is based on partial hypotheses: - There is a relationship between family factors and the violence of the student against the professor. - There is a relationship between school factors and student violence against the professor. - There is a relationship between the economic factors and the violence of the student against the professor. The questionnaire was a key tool to achieve the objectives of this study and to reach a scientific result based on theoretical construction and field study. The questionnaire included 36 questions. This tool was applied to an objective sample of the valley state , And may be the study community of (100) professor and professor. Through the study we reached: There is a relationship between family factors and violence against pupils against the professor family problems contribute significantly to violence. - There is no relationship between economic factors violently student against the professor. - There is a relationship between the school factors violently student against the professor because the latter does not understand the problems
من وجهة نظر الأساتذة ببعض المتوسطات بولاية الوادي
مذكرة ماستر علوم اجتماعية تخصص علم اجتماع التربية
Keywords: العنف المدرسي; Violence scolaire; School violence